Mesozooplankton biovolume and normalized biovolume size spectra under the Amazon River Plume influence measured during cruise Camadas Finas III - Claudeilton Severino de Santana (PANGAEA, 2024)
Zooplankton samples were collected in October 2012 aboard the Camadas Finas III cruise, using bongo nets with a 300 μm mesh size. The cruise followed the distribution of the Amazon River Plume across coastal and oceanic waters during the retroflection period of the North Brazil Current. For each sample, size fractions (>1 mm and <1 mm) were digitized using a ZooScan device (resolution: 2400 dpi) and analyzed using ZooProcess software. Images were counted, measurements were estimated, and data were organized into size bins. All living particles were subjected to quality control protocols established by The Pelagic Size Structure Database (PSSdb; https://pssdb.net/). A lower threshold of 600 μm was defined, while the upper threshold was determined by the largest size class prior to three consecutive empty size classes. Particles within these thresholds were used to estimate abundance, biovolume, biomass, and Normalized Biovolume Size Spectra (NBSS). For different taxonomic units, these data are summarized in the respective columns, except for NBSS results, which are presented as values per sample in the columns labeled extquotesingleSlope, extquotesingle extquotesingleIntercept, extquotesingle and extquotesingleR^2. extquotesingle